Distance Response of Sal Heartwood Borer, Hoplocerambyx spinioornis Newman (Cerambycidae: Coleoptera) to Freshly Felled Sal Trees - , Pratap; Ram, Dna; Misra, Mohan (Indian Forester, 1981)
Odour guides sal heartwood borer to its food, borer and exlpe it to locate appropriate place for oviposition Distance response eXperiment conducted in sal forest revealed that the beetles can locate a freshly felled sal tree from a maximum distance of 2000 m. Ratio of sexes reaching the traps waa 1 : 1.